Host-Pathogen Interactions of Mycoplasma mycoides in Caprine and Bovine Precision-Cut Lung Slices (PCLS) Models - Weldearegay, Yenehiwot; Müller, Sandy; Hänske, Jana; Schulze, Anja; Kostka, Aline; Rüger, Nancy; Hewicker-Trautwein, Marion; Brehm, Ralph; Valentin-Weigand, Peter; Kammerer, Robert; Jores, Joerg; Meens, Jochen (MDPI, 2019)
Respiratory infections caused by mycoplasma species in ruminants lead to considerable economic losses. Two important ruminant pathogens are Mycoplasma mycoides subsp. Mycoides (Mmm), the aetiological agent of contagious bovine pleuropneumonia and Mycoplasma mycoides subsp. capri (Mmc), which causes pneumonia, mastitis, arthritis, keratitis, and septicemia in goats. We established precision cut lung slices (PCLS) infection model for Mmm and Mmc to study host-pathogen interactions. We monitored infection over time using immunohistological analysis and electron microscopy. Moreover, infection burden was monitored by plating and quantitative real-time PCR. Results were compared with lungs from experimentally infected goats and cattle. Lungs from healthy goats and cattle were also included as controls. PCLS remained viable for up to two weeks. Both subspecies adhered to ciliated cells. However, the titer of Mmm in caprine PCLS decreased over time, indicating species specificity of Mmm. Mmc showed higher tropism to sub-bronchiolar tissue in caprine PCLS, which increased in a time-dependent manner. Moreover, Mmc was abundantly observed on pulmonary endothelial cells, indicating partially, how it causes systemic disease. Tissue destruction upon prolonged infection of slices was comparable to the in vivo samples. Therefore, PCLS represents a novel ex vivo model to study host-pathogen interaction in livestock mycoplasma.